The Role of Patient Satisfaction in Mediating Quality and Accessibility to Health Service Utilization - Anak Agung Diah Ratna Dewi; Gregorius Paulus Tahu; I Gusti Ngurah Agung Gede Teja Kusuma; Pande Ketut Ribek (AIBPM Publisher, 2025)
Concerns regarding patient satisfaction at Kasih Ibu Denpasar Hospital indicate potential issues related to service quality and accessibility. This study aims to examine the mediating role of patient satisfaction in the relationship between service quality, service accessibility, and health service utilization. A quantitative approach was employed involving 82 outpatient respondents, with data collected through structured questionnaires. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used for data analysis. The results show that service quality has a strong and significant effect on patient satisfaction (? = 0.728; p 0.001), as does service accessibility (? = 0.233; p 0.01). Service quality does not have a significant direct effect on health service utilization (? = 0.020; p 0.05), whereas service accessibility has a significant positive effect (? = 0.454; p 0.001). Patient satisfaction also significantly influences health service utilization (? = 0.167; p 0.05). Mediation analysis indicates that patient satisfaction fully mediates the relationship between service quality and utilization and partially mediates the relationship between service accessibility and utilization. These findings highlight the importance of improving service quality, accessibility, and patient experience to enhance health service utilization.